Approaches to the Development of Business Growth Strategy - Malynovskyy, Jurij; Petryshyn, Natalia; Malynovska, Julia; Oliinyk, Andrij (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
This article investigates the theoretical foundations of structural characteristics and the choice of business growth strategy as an important managerial factor of its effective operation. The approaches to strategy development are subjected to generalization. It is shown that strategy is the directing vector of factory management and its production and business operations in the modern globalized, dynamic and competitive market environment